Miss gay : o protagonismo gay e os atos performáticos de gênero - Santos, Muryllo Rhafael Lorensoni do (2021)
This essay aims to discuss the aspects related to social actions in terms of emphasis gay protagonism, in particular transformists of beauty contests called Miss Gay contests. All the reflections presented here seek to comprehend the own logic used in those fair, which operates from a concept articulation linked to social markers of difference, as genre, sexuality, race, class, generation, and ethnicity. In an ethnographic aspect, the autoethnographic is configured through a transformist experience at Miss Mato Grosso Gay 2018 content in Cuiabá-MT, based on the exercise of dense description. It is necessary to mention that this decolonizes research, inserted in theorical field of cultural studies, anthropology and studies of genre and sexuality based on queer analytic, identified by surveys which focuses on a discussion how the articulation of gender relatives’ concepts can create masculinity and femininity performing ideals in beauty contents (and performance). I propose the investigation of transformism, in order to cast another look at the subjective experiences, once it amplifies the sexuality and genres meanings shared intersubjectively in located scenarios, thus perceive those contexts as creation gaps of a new social significance through performance acts, particular kind of beauty representation and the values shrouded in this process. This project responds to numerous recent researches, however, support a little explored object. The gay universe focusses on the tradition and reproduce in an arbitrary way the steps of this ritual, which is the Miss content, giving a new significance to the staging as a gay empowerment space and genre construction. Different from normative contests, the Miss Gay competition highlight the homosexual (transformist) giving to this category a protagonism moment, where some social conjectures are re-signified in such a context. The homosexual militant movement and the social paradigms changes point out new angles by which those the gender could be observed as a social fiction, that has been appropriated by the transformers as a way of contesting and resistance.